Design Of An Employee Performance Assessment System At Pt. Tritan Metalindo Successful - Evi Silvana Muchsinati; Monica Ella (Universitas Internasional Batam, 2024)
The aim of this activity is to help the company implement a performance appraisal system for all PT employees. Tritan Metalindo Success. Performance appraisals help companies make decisions with accurate and objective assessment results and help companies make decisions regarding career development for employees or even dismissal. Apart from that, it increases employee motivation to work better and meet the performance standards that have been set to achieve company goals. The method used is to provide output in the form of performance assessment indicators and work assessment forms that the company will use. The results of the activities were changes in the performance of the company's employees which increased due to increased productivity and profits at PT. Tritan Metalindo Success. Then one of the problems that occurred in the company was that the company's turnover rate decreased to only 7%, where there was an increase in the quality of employee work in the company